Impact of Customer Satisfaction on Loyalty in Indonesia B2B Digital Marketing Agency (Case Study of Bertumbuh Creative) - Adhyaksa, Rangga Pijar; Astuti, Novika Candra (Jurnal Sosial Teknologi, 2025)
This study examines the factors influencing customer satisfaction and loyalty at Bertumbuh Creative, a micro-scale B2B digital agency in Indonesia's rapidly growing digital economy. With the e-commerce sector projected to reach $360 billion in GMV by 2030, Bertumbuh Creative provides cost-efficient services to MSMEs, including social media management, e-commerce activation, and digital advertising. Despite successful client acquisition and regional expansion, the agency faces challenges in maintaining customer retention, signaling underlying issues with satisfaction and operational consistency. Using a qualitative research approach, this study applies the Gioia Method and Van Rensburg’s (2010) Overall Satisfaction framework to explore the drivers of customer satisfaction. In-depth interviews with clients reveal that satisfaction is influenced by both functional execution and relational surplus, such as emotional attentiveness and fair negotiation. However, recurring technical inconsistencies negatively impact trust and perceived value. Loyalty mapping using Dick and Basu’s (2021) typology shows that while most clients exhibit latent loyalty, their positive attitudes are not reflected in repeat behavior, indicating a need for more structured retention strategies. The findings suggest that Bertumbuh Creative must address operational inconsistencies and enhance relational aspects to improve customer loyalty and retention. Future research should explore structured retention strategies and the role of operational consistency in customer satisfaction in the digital services sector.